2008
DOI: 10.1055/s-2008-1038459
|View full text |Cite
|
Sign up to set email alerts
|

Aktuelle Übersicht zum Dermisersatz mit Kollagen-Elastin-Matrix Matriderm® bei Brandverletzungen

Abstract: Matriderm is a dermal substitute consisting of a native (non-cross-linked) collagen matrix supplemented by a elastin hydrolysate. It is available in sheets of 1 mm and 2 mm thickness, and may be covered in a single step procedure with immediate split thickness skin grafting. Duration of the surgical procedures are only marginally increased. There is no diminished take of split thickness graft and only marginally prolonged healing time compared with the split thickness graft only. In experimental models the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…With the progression of healing process, fibroblasts lay down the ECM and the Matriderm ® resorbs [109]. Permacol has a good aesthetic and functional outcome but is prone to infection, hematomas, and seromas [73,74], whereas, Matriderm involves a single stage procedure with increased vascularization and elasticity of regenerating tissue but lacks enough scientific evidence to verify its efficacy of a one-step procedure [103,110,111]. Another substitute is Oasis, which is derived from porcine intestinal submucosa [79,85].…”
Section: Types Of Skin Substitutesmentioning
confidence: 99%
“…With the progression of healing process, fibroblasts lay down the ECM and the Matriderm ® resorbs [109]. Permacol has a good aesthetic and functional outcome but is prone to infection, hematomas, and seromas [73,74], whereas, Matriderm involves a single stage procedure with increased vascularization and elasticity of regenerating tissue but lacks enough scientific evidence to verify its efficacy of a one-step procedure [103,110,111]. Another substitute is Oasis, which is derived from porcine intestinal submucosa [79,85].…”
Section: Types Of Skin Substitutesmentioning
confidence: 99%
“…[27] In experimental models, the matrix reduces wound contracture, and histologically collagen bundles in the scar are more randomly orientated. Clinical trials with a long-term clinical evaluation showed no difference in scar elasticity between the described dermal substitute and split thickness grafts alone.…”
Section: Classificationsmentioning
confidence: 99%
“…Current indications for Matriderm are extensive cutanenous defects, like second- to third-degree burn wounds, large decollements or the revision of large, adherent scars [4,5,6]. Our case demonstrates that it is also possible to use a combination of Matriderm with autologous split-skin grafts to cover deep wounds with exposed tendons resulting in an excellent functional and cosmetic outcome.…”
Section: Discussionmentioning
confidence: 80%